2011
DOI: 10.4236/aces.2011.13014
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Ethanol and Hydrogen by Glycerol Fermentation Using <i>Escherichia coli</i>

Abstract: Production of high value products from glycerol via anaerobic fermentation is of utmost importance for the biodiesel industry. The microorganism Escherichia coli (E. coli) K12 was used for fermentation of glycerol. The effects of glycerol concentration and headspace conditions on the cell growth, ethanol and hydrogen production were investigated. A full factorial experimental design with 3 replicates was conducted in order to test these factors. Under the three headspace conditions tested, the increase of glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The fermentation of glycerol using Escherichia coli K12 also revealed that a maximum ethanol yield of 0.40 g/g glycerol was obtained when 10 g/L concentration of glycerol was used under membrane headspace conditions [88]. Similarly, Loaces et al [95] used E. coli to improve ethanol production and glycerol conversion using heterologous genes (metagenomic fragment) obtained from anaerobic purge sludge.…”
Section: Ethanolmentioning
confidence: 99%
See 1 more Smart Citation
“…The fermentation of glycerol using Escherichia coli K12 also revealed that a maximum ethanol yield of 0.40 g/g glycerol was obtained when 10 g/L concentration of glycerol was used under membrane headspace conditions [88]. Similarly, Loaces et al [95] used E. coli to improve ethanol production and glycerol conversion using heterologous genes (metagenomic fragment) obtained from anaerobic purge sludge.…”
Section: Ethanolmentioning
confidence: 99%
“…The use of microorganisms to produce hydrogen has also been studied and reported over the years, and findings have shown enhanced crude glycerol utilization without undergoing the high cost of the purification process associated with having pure glycerol. The use of Enterobacter spH1, Enterobacter spH2 and Citrobacter freundii H3 [87], Escherichia coli K12 [88], Clostridium freundii H3 [89], Klebsiella pneumonia TR 17 [90], Thermotoga maritime and Thermotoga neapolitana [91] have shown relatively large quantities of H 2 (>70%) under varying conditions. However, the details of microbial hydrogen production are beyond the scope of this review.…”
Section: Ethanolmentioning
confidence: 99%
“…Glycerol is a by-product of biodiesel production, produced in large quantities and discarded as waste in Africa. However, glycerol can be converted directly to ethanol (Chaudhary et al, 2011) or applied as organic co-solvent in biomass pretreatment (Lynam and Coronella, 2014). Though majority of glycerol pretreatment studies have focused on elevated temperatures (170-400 o C) (Martin et al, 2015;Martín et al, 2011;Romani et al, 2013), their applications at moderate temperatures have not been given much attention.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Many facultative anaerobes are able to co-produce hydrogen and ethanol, such as Klebsiella sp. (Wu et al 2011), Enterobacter aerogenes (Ito et al 2005;Jitrwung and Yargeau 2011;Reungsang et al 2013;Sakai and Yagishita 2007) and Escherichia coli (Chaudhary et al 2011;Hu and Wood 2010;Murarka et al 2008;Yoshida et al 2006). Examples of the utilization of facultative anaerobes in hydrogen and ethanol fermentation are provided in Table 1.…”
Section: Metabolic Properties Of Facultative Anaerobesmentioning
confidence: 99%